Robust Real Rate Rules - Tom D. Holden (ZBW - Leibniz Information Centre for Economics, 2024)
Central banks wish to avoid self-fulfilling fluctuations. Interest rate rules with a unit response to real rates achieve this under the weakest possible assumptions about the behaviour of households and firms. They are robust to household heterogeneity, hand-to-mouth consumers, non-rational household or firm expectations, active fiscal policy and to any form of intertemporal or nominal-real links. They are easy to employ in practice, using inflation-protected bonds to infer real rates. With a time-varying short-term inflation target, they can implement an arbitrary inflation path, including optimal policy. This provides a way to translate policy makers' desired path for inflation into one for nominal rates. US Federal Reserve behaviour is remarkably close to that predicted by a real rate rule, given the desired inflation path of US monetary policy makers. Real rate rules work thanks to the key role played by the Fisher equation in monetary transmission.
Keywords: E52; E43; E31; 330; robust monetary rules; determinacy; Taylor principle; inflation dynamics; transmission mechanism